Pemanfaatan Tepung Kulit Pisang Dalam Pembuatan Kue Cucur - Ramon Hurdawaty; Katharina Ngana (Politeknik Sahid, 2020)
Cucur cake is one of a variety of traditional cake preparations commonly found in several areas such as East Nusa Tenggara. This round cucur cake has a very sweet taste which is processed by frying it. The main ingredients in making bowsprit cake are wheat flour and rice flour. Not only wheat flour as the main ingredient in making cakes, but wheat flour can also be substituted for banana peel flour. The research objective with the addition of banana peel flour is to improve traditional cake processing by not eliminating the basic ingredients for making Cucur cakes, but using banana peel flour as an additional ingredient in making cucur cakes as a legacy of traditional cake processing. The manufacture of banana peel flour is done to reduce waste disposal products and can be used as a valuable value if it can be processed properly and correctly. This research was conducted by measuring the level of preference and sensory attributes of the aroma, color, taste, texture of the Cucur cake using banana peel flour. In making Cucur cake using banana peel flour using an experimental method. In addition, the design used was a completely randomized design using three repetitions with a concentration of 0% control, 25% banana peel flour, 50% banana peel flour and 75% banana peel flour. The results showed that the sensory bowsprit with the use of banana peel flour produced the highest value with an average value of 3.12 found in the 25% sample of banana peel flour with very blackish brown color parameters, a little taste of banana peel, a slight aroma of banana peel and with no hard texture.